(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article examines the techniques of playing the dutar, one of Uzbekistan’s national string instruments, with a particular focus on teaching methods, preserving and developing the classical maqom tradition, and refining students’ instrumental performance skills. It also discusses the transmission of this rich heritage to future generations.